Connectors for electrical and electronic equipment. Product requirements. Power connectors. Detail specification for 2P+PE circular connectors with 20 A rated current and push-pull locking IP65/IP67 with metal housing Part 8-103, (26th June 2023) - British Standards Institution,
No abstract available